(untitled) (مجلة العلوم الشاملة, 2026)
​This study aims to explore and understand the potential role of a "carbon tax" as a fiscal policy tool in guiding and incentivizing administrative decisions toward adopting renewable energy projects within the General Electricity Company of Libya (GECOL). The study stems from a research gap identified in the researcher’s previous work, which confirmed that a "lack of specialized expertise" represents a significant obstacle to energy transition. Therefore, this research seeks to analyze this obstacle from a behavioral management perspective. Using a qualitative approach based on case studies, in-depth personal interviews were conducted with a purposive sample of six department managers, decision-makers, and technical experts from GECOL and the Renewable Energy Authority. The thematic analysis of the interviews revealed that the awareness of the financial costs of carbon emissions acts as a "cognitive motivator" that accelerates administrative acceptance of green projects. However, this awareness is hampered by "organizational rigidity" and conflicting institutional authorities. The interviews also revealed that the lack of "expert capabilities" is not merely a technical obstacle, but a bottleneck preventing leaders from making bold decisions toward a "prosumer" model. The study recommends the development of a legislative framework that unifies efforts among sovereign institutions, with a focus on investing in "specialized human capital" as a prerequisite for the success of any green fiscal policies in the Libyan context.